High-Fidelity Lumped-Parameter Thermal Models for Assessing Cooling Techniques of PMSMs in EV Applications - Dawei Liang; Zi Qiang Zhu; Ankan Dey (CES Transactions on Electrical Machines and Systems)
This paper presents a high-fidelity lumped-parameter (LP) thermal model (HF-LPTM) for permanent magnet synchronous machines (PMSMs) in electric vehicle (EV) applications, where various cooling techniques are considered, including frame forced air/liquid cooling, oil jet cooling for end-winding, and rotor shaft cooling. To address the temperature misestimation in the LP thermal modelling due to assumptions of concentrated loss input and uniform heat flows, the developed HF-LPTM introduces two compensation thermal resistances for the winding and PM components, which are analytically derived from the multidimensional heat transfer equations and are robust against different load/thermal conditions. As validated by the finite element analysis method and experiments, the conventional LPTMs exhibit significant winding temperature deviations, while the proposed HF-LPTM can accurately predict both the midpoint and average temperatures. The developed HF-LPTM is further used to assess the effectiveness of various cooling techniques under different scenarios, i.e., steady-state thermal states under the rated load condition, and transient temperature profiles under city, freeway, and hybrid (city + freeway) driving cycles. Results indicate that no single cooling technique can maintain both winding and PM temperatures within safety limits. The combination of frame liquid cooling and oil jet cooling for end winding can sufficiently mitigate PMSM thermal stress in EV applications.